STUDI KOMPARASI TEORI KETELADANAN NASHIH ULWAN DAN TEORI KOGNITIF SOSIAL ALBERT BANDURA - Yusuf Rendi Wibowo; Fatonah Salfadilah; Moch. Farich Alfani (PGMI, STAI Miftahul Ula Nganjuk, 2023)
This research aims to explore Nashih Ulwan's exemplary role model theory and Albert Bandura's social cognitive learning theory. The research method used is qualitative research, and the type of research is library research. The method used in this research is the hermeneutic method. The results of this research show that according to Abdullah Nashih Ulwan, exemplary role modeling is the most effective way to prepare a child's character, shape their social soul and feelings. On the other hand, according to Bandura's social cognitive theory, a person can learn by observing and imitating the behavior of others around them. The similarity between these two theories lies in the fact that learning is a process of observation and attention, where a person learns from their environment, in terms of models, examples or exemplary role models. The difference lies in Nashih Ulwan's emphasis on following the exemplary role model of Prophet Muhammad, while Bandura's theory focuses on children observing the behavior of adults towards an object (doll), and the different factors that are not imitated or followed from the observed model.